'To be a woman is to make a plan': a qualitative study exploring mothers' experiences of the Child Support Grant in supporting children's diets and nutrition in South Africa. Issue 4 (24th April 2018) - Zembe-Mkabile, Wanga; Surender, Rebecca; Sanders, David; Swart, Rina; Ramokolo, Vundli; Wright, Gemma; Doherty, Tanya
Abstract : Food security and good nutrition are key determinants of child well-being. There is strong evidence that cash transfers such as South Africa's Child Support Grant (CSG) have the potential to help address some of the underlying drivers of food insecurity and malnutrition by providing income to caregivers in poor households, but it is unclear how precisely they work to affect child well-being and nutrition. We present results from a qualitative study conducted to explore the role of the CSG in food security and child well-being in poor households in an urban and a rural setting in South Africa. Setting: Mt Frere, Eastern Cape (rural area); Langa, Western Cape (urban township). Participants: CSG recipient caregivers and community members in the two sites . We conducted a total of 40 in-depth interviews with mothers or primary caregivers in receipt of the CSG for children under the age of 5 years. In addition, five focus group discussions with approximately eight members per group were conducted. Data were analysed using manifest and latent thematic content analysis methods. Results: The CSG is too small on its own to improve child nutrition and well-being. Providing for children's diets and nutrition competes with other priorities that are equally important for child well-being and nutrition. Conclusions: In addition to raising the value of the CSG so that it is linked to the cost of a nutritious basket of food, more emphasis should be placed on parallel structural solutions that are vital for good child nutrition outcomes and well-being, such as access to free quality early child development services that provide adequate nutritious meals, access to adequate basic services and the promotion of appropriate feeding, hygiene and care practices.